Percentage arterial enhancement on 2D CT in the diagnosis of primary hyperparathyroidism: A prospective validation study and potential pitfalls. Issue 8 (31st May 2022) - Sonawane, Sushil; Jadhav, Swati S.; Goroshi, Manjunath; Krishnappa, Brijesh; Sharma, Anima; Hira, Priya; Garle, Mahadev N.; Gosavi, Vikrant; Memon, Saba; Patil, Virendra A.; Lila, Anurag R.; Shah, Nalini; et al.
Abstract: Background: Parathyroid lesions are identified by subjective enhancement and washout patterns on computed tomography (CT). We have previously proposed "percentage arterial enhancement" (PAE) as an objective index and now aim to validate its performance prospectively. Methods: Dual‐phase CT was performed in 40 consecutive primary hyperparathyroidism patients. PAE was calculated as [arterial phase Hounsfield unit (HU)‐unenhanced phase HU/unenhanced phase HU] × 100. PAE > 128.9% was considered parathyroid. Results: PAE had 94.2% sensitivity, 100% positive predictive value (PPV) in lateralization, and sensitivity and PPV of 93.9% in quadrant localization of single‐gland disease. PAE failed to identify two lesions: an intrathyroidal parathyroid carcinoma in the background of multinodular goiter and another lower enhancing cystic parathyroid adenoma. PAE had 60% sensitivity, and 100% PPV to identify multigland disease. The mean effective dose was 2.74 mSV. Conclusions: PAE is a specific CT index for parathyroid lesions with less radiation exposure. Areas of caution include intrathyroidal and cystic lesions.